INTERPERSONAL MEANING BASED ON APPROBATION MAXIM AND GENRE ANALYSIS OF SIXTH STUDENTS’ WRITING MASTERPIECE OF ENGLISH EDUCATION PROGRAM OF STKIP PGRI PACITAN - Agung Budi Kurniawan (LPPM Press STKIP PGRI Pacitan, 2016)
This research focuses on three main data findings and analysis. It is analysis of genre applied, analysis of the application of approbation maxim, analysis of the interpersonal meaning. This research was conducted by applying a modification of one shot case study of experiment. The subject is 20 students. They are sample taken by purposive sampling technique. It takes data from 20 student’s writing masterpiece of scientific papers. It is the final task of scientific writing subject of 6th semester of English education department of STKIP PGRI Pacitan in the academic year 2015-2016. One important notice is that the data analysis is only the background of the study of the writing, so it is not the entire writing masterpiece. The researcher is the subject’s lecturer. The treatment is the classroom teaching learning process. The main analysis reflects that every student has different character of writing. Writing scientific paper reflects the writer’s personality, knowledge, skill, competency, and intention. Some conclusions from this research are: 1).Background of the study of a scientific paper follows only one certain genre, 2).The genre of a background of the study of a scientific paper cannot be determined which one is the best or a must because it is a writer’s or researcher’s authority to express his or her mind and facts, 3).It cannot be denied that the application of approbation maxim can help a writer to be close with readers, 4).Interpersonal meaning inside of a background of the study reflects some points include a researcher’s or writer’s ideas, opinions, experiences, future view points, and linguistic competency.